Deciduous material contribution and soil nutrients in eucalyptus plantations and secondary forest - Diniz, Anderson Ribeiro (2011)
In this study we evaluated the uptake, decomposition and nutrient release of the deciduous material in summer in areas of secondary forest and eucalyptus plantations in Redenção da Serra, SP. Were installed ten collectors in each area to evaluate the contribution of deciduous material (litter). It was collected every 15 days from December 2003 for 75 days. Part of the litter was placed in decomposition bags and distributed in surface areas, being collected every 15 days for evaluation. The area under eucalyptus showed greater intake of dry matter, lower decomposition constant and longer half life. There was a higher proportion of the fraction in the forest leaves and branches on the fraction area of eucalyptus. At time zero, the area of secondary forest showed higher accumulation of N, K, Ca, Mg and P. As for the area of eucalyptus, there was a sequence of N, Ca, K, Mg and P. At the end of 75 days, the area of eucalypt in plantation showed higher percentages of N, P, K and Ca. For the climatic conditions of Redenção da Serra, in summer, the area with eucalyptus showed greater intake of dry matter and nutrient content remaining compared with the area of forest.